Charakterystyka elektroforetycznej ruchliwości jąder komórkowych (EMN) u trenujących dziewcząt - Czapla, Zbigniew; Szczepanowska, Ewa (Tower Press Sopot, 2006)
Metabolic activity of cells could be describe by changes of an index of Electrophoretic Mobility of Cell Nuclei (EMN) in epithelium cells. The examined group (N = 33) consisted of female juniors practicing rowing. In this study 3 exercise tests of an increasing intensity up to: anaerobic threshold, maximal oxygen uptake and supermaximal intensity were applied. Values of EMN index reflected an influence of physical exercise on metabolic status of an organism determining a concentration of acidic intermediates. Changes of EMN index were connected with the metabolic threshold of anaerobic processes indicating the oxygen potential of an organism. EMN index could be used as an additional parameter to evaluate physiological changes under the influence of physical exercise. In an aspect of the level of performance it could be helpful in evaluation of physiological changes during training process.
Characteristics of Electrophoretic Mobility of Cell Nuclei in female athletes
Keywords: physical exercise; metabolic status; EMN index; training process; wskaźnik EMN; wysiłek fizyczny; wioślarki; przemiany metaboliczne